Strukturasi Makna Budaya dalam Kepemimpinan Adat Melayu, Sakai, dan Talang Mamak untuk Tata Kelola Hutan Riau - Eno Suwarno; M. Rawa El Amady (Universitas Andalas, 2026)
The province of Riau presents a paradox between economic growth and deforestation, a conflict rooted in the struggle between the forest as an extractive space and a culturally meaningful place. This systematic review analyzes how cultural meaning systems are structured within the indigenous leadership of three Riau communities, Malay, Sakai, and Talang Mamak, and how these meanings are reproduced or transformed in forest governance. Integrating Clifford Geertz's interpretive anthropology with Anthony Giddens' structuration theory, we synthesized 68 academic documents published between 1973-2026. The analysis reveals three leadership typologies: hierarchical-genealogical (Malay), centered on sako datuk titles and the